Association of third-trimester abdominal circumference with provider-initiated preterm delivery - Hawkins, Leah K. (J Matern Fetal Neonatal Med, 2013)
OBJECTIVE: Evaluate the association of a small third-trimester abdominal circumference (AC < 10th percentile) in the setting of a normal estimated fetal weight (EFW ≥ 10th percentile) with gestational age at delivery, indication for delivery and neonatal outcomes. METHODS: Retrospective cohort study at an academic hospital of women with singleton pregnancy seen for ultrasound from 28+0-33+6 weeks of gestation during 2009-2011. Outcomes were compared between two groups: normal AC (AC and EFW ≥ 10th percentile) and small AC (AC < 10th percentile and EFW ≥ 10th percentile). RESULTS: Among 592 pregnancies, fetuses in the small AC group (n = 55) experienced a higher incidence of overall preterm delivery (RR: 2.2, 95% Cl: 1.3–3.7) and provider-initiated preterm delivery (RR: 3.7, Cl: 1.8–7.5) compared to those in the normal AC group (n = 537). Neonates in the small AC group had a lower median birth weight whether delivered at term (p < 0.001) or preterm (p = 0.04), but were not more likely to experience intensive care unit admission or respiratory distress syndrome (all p ≥ 0.35). CONCLUSIONS: Small AC, even in the setting of an EFW ≥ 10th percentile, was associated with a higher incidence of overall and provider-initiated preterm delivery despite similar neonatal outcomes. Further investigation is warranted to determine whether these preterm deliveries could be prevented.